Nazwy własne w literaturze dziecięcej Rogera Hargreavesa w tłumaczeniu Marcina Wróbla - Łuc, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The subject of the analysis presented in the article were personal names and toponyms derived from 42 stories by Roger Hargreaves addressed to children aged 4–6. The description of proper names in the British writer’s works is based on the assumption that the translator fully understood and faithfully reflected the author’s intentions, taking into account the functionality of the cycle of stories and the age of the recipient, and that his goal was to faithfully translate the senses contained in the semantics/sound of the created onyms. The study aimed to capture the mechanisms of creating proper names and the ways of introducing onyms into the text. The article also describes an onymic strategy consisting of a syntactic and semantic juxtaposition of anthroponyms with toponyms which serves to complete the characterisation of the heroes and the construction of the literary world. The names extracted from Hargreaves’s works were considered in terms of their textual and semiotic structures, in both the motivational and pragmatic dimensions. A semanticpragmatic analysis of the names showed that the onyms invented by the author/translator were created as series. Within the creative models used by him, the following stand out due to their frequency: names derived using suffixes, names created with the use of an appellative used specifically for naming people – pan [mister], formations composed with the lexeme mały [small] and items created by means of onymisation.